(untitled) (Innovation & Development in Engineering and Applied Science, 2025)
The implementation of an "Innovation in Public Services: Web Application for Citizen Revenue Collection with ISO/IEC 25010 Focus" arises as an essential measure to address the challenges inherent in the manual collection process of citizen services: drinking water, drinking water service installation, connection maintenance, reconnection of connections, garbage collection, sewerage, in society. The adoption of SCRUM, recognized for its agile and adaptable approach, is key to the execution of this project. By employing SCRUM, effective process management is facilitated, with iterative deliveries and close collaboration between developers and end users. This iterative approach allows for continuous adjustments and improvements during development, ensuring that the final platform meets the specific needs of the Santo Domingo N°1 community in the province of Pichincha, Cayambe canton. By integrating SCRUM and usability metrics in accordance with ISO/IEC 25010, the aim is not only to speed up payment processes but also to provide high-quality software that meets the expectations of partners and local authorities.